Biofabrication of a novel biomolecule-assisted reduced graphene oxide: an excellent biocompatible nanomaterial - Zhang X (Dove Medical Press, 2016)
Xi-Feng Zhang,1 Sangiliyandi Gurunathan2 1College of Biological and Pharmaceutical Engineering, Wuhan Polytechnic University, Wuhan, People’s Republic of China; 2Department of Stem Cell and Regenerative Biotechnology, Konkuk University, Seoul, Republic of Korea Abstract: Graphene has been shown much interest, both in academics and industry due to its extraordinary physical, chemical, and biological proprieties. It shows great promises in biotechnological and biomedical applications as an antibacterial and anticancer agent, nanocarrier, sensor, etc. However, many studies demonstrated the toxicity of graphene in several cell lines, which is an obstacle to its use in biomedical applications. In this study, to improve the biocompatibility of graphene, we used nicotinamide (NAM) as a reducing and stabilizing agent to catalyze the reduction of graphene oxide (GO) to reduced graphene oxide (rGO). The resulted smaller-sized GO (NAM-rGO) showed excellent biocompatibility with mouse embryonic fibroblast cells, evidenced by various cellular assays. Furthermore, NAM-rGO had no effect on mitochondrial membrane permeability and caspase-3 activity compared to GO. Reverse transcription polymerase chain reaction analysis allowed us to identify the molecular mechanisms responsible for NAM-rGO-induced biocompatibility. NAM-rGO significantly induced the expression of genes encoding tight junction proteins (TJPs) such as zona occludens-1 (Tjp1) and claudins (Cldn3) without any effect on the expression of cytoskeleton proteins. Furthermore, NAM-rGO enhances the expression of alkaline phosphatase (ALP) gene, and it does this in a time-dependent manner. Overall, our study depicted the molecular mechanisms underlying NAM-rGO biocompatibility depending on upregulation of TJPs and ALP. This potential quality of graphene could be used in diverse applications including tissue regeneration and tissue engineering. Keywords: biocompatibility, graphene oxide, nicotinamide, reduced graphene oxide, tight junction proteins, alkaline phosphatase